1500-nm Q-switched fibre laser with carbon nanotubes - Muhammad, Farah Diana; Zulkifli, Mohd Zamani; Ahmad, Harith (Turpion, 2018)
A Q-switched fibre laser operating at 1500 nm is proposed and demonstrated. The laser uses a saturable absorber (SA) based on carbon nanotubes (CNTs) to generate Q-switched pulses, while a 30-m-long depressed-cladding erbium-doped fibre (DC-EDF) provides the necessary gain in the desired wavelength region. The proposed laser has lasing and pulsed thresholds of 30 mW and 50 mW respectively, along with a maximum output power, pulse energy and peak power of 0.5 mW, 7.6 nJ and 2.2 mW. Additionally, the output of the system also has a maximum repetition rate of 59.4 kHz with the shortest pulse duration measured at 3.4 ms. The output pulses are smooth and uniform, with no indication of self mode-locking.